Preparation of Islamic Religious Education Teachers in Secular Countries: A Study in Austria - Munadi, Muhammad (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Especially in Austria itself, it is estimated that in 2050 the Muslim population will be around 19.9% of the total population and the population increase will be second in Europe after Sweden with 30.6%. Interestingly again in Austria apart from being a secular country but it provides concern for Muslims to develop Islamic religious education there. Therefore, this study aimed to determine how universities in Austria prepared Islamic religion teachers at undergraduate level both in terms of models and curricula to face increasingly complex challenges and a growing number of Muslim citizens. This study used library research, while the approach used interpretative approach. The main reference source was the content on the university website that offers Islamic Religious Education programs. In addition, various sources lead to discourse and curriculum development in Austria. The number of data were displayed using descriptive statistics and described using descriptive qualitative. Then research design that would be carried out was to reveal the course content contained in the web and then reduced, especially in terms of the preparation curriculum for Islamic Religious Education teachers. Of the various courses presented were analyzed using content analysis where the important point was to take the most fundamental content that was related to the principles of curriculum development, namely contextual and responding to the challenges of the times. The results showed that the preparation of Islamic teachers in one of the colleges in Austria consists of undergraduate, graduate, and postgraduate degrees. Undergraduate program of Islamic Religious Education consists of two models, namely Bachelor’s Program Secondary School Teacher Training (General Education) – Subject: Islamic Religion and the specific name is Bachelor’s Program - Islamic Religious Education. In general, the content emphasis applied in the preparation of Islamic religious education teachers is still material-based.